Pengembangan Kapasitas Residen dengan Metode Therapeutic Community di Panti Rehabilitasi Narkoba Ar-Rahman Palembang - Aidil Fitri; Sriati; Yoyok Hendarso (Syntax Corporation, 2023)
Drug abuse, psychotropics, and other addictive substances have increased in Indonesia. Drug abuse can pose a serious threat to social life and health in society. The National Narcotics Agency of South Sumatra Province recorded that the prevalence of drug abuse throughout 2021 reached 5.5 percent or as many as 359,363 people from the total population of South Sumatra Province. This figure is the second highest in Indonesia. There is a need for a social movement from the government or society to overcome the problem of drug abuse. An independent society is a society that has good capacity. Capacity building to develop the quality of personal characteristics to be more effective and efficient both in the entity and global scope. The research aims to determine the process of capacity building of residents with the Therapeutic Community method at the Ar-Rahman Palembang Drug Rehabilitation Center. Qualitative research method with descriptive qualitative type through phenomenological research strategy. Research informants consist of key informants, key informants and supporting informants. The residents become the unit of data analysis. Data collection techniques through observation, documentation, and interviews. Technical data analysis through the process of data collection, data coding, data presentation and conclusions. The process of the Therapeutic Community Method focuses on coaching which includes 4 main things, namely: (1) changing behavior, (2) controlling emotions and thoughts, (3) growing spiritually and intellectually, and (4) being able to survive and be independent